Individual Factors Affecting Research misconduct in Iranian Higher Education System - Heydar Choupani; Sayyed Ali Siadat; Saeed Rajaeepour (International Review of Management and Marketing, 2018)
Research misconduct is one of the problems that today's academic community is involved in and must recognize its causes and roots in order to provide solutions. In this study, we examine the individual factors affecting the Research misconduct. The research method is objective, applied and in terms of collecting data, is descriptive-causal. The statistical population of the study consisted of all faculty members, senior students and Ph.D. Students of Isfahan University of Isfahan (Isfahan University, Isfahan University of Technology, Art University and the University of Medical Sciences) were 20487 that 377 person were selected as the statistical sample using stratified sampling and through the Cochran sampling formula. To collect data, a questionnaire extracted from the interview is used. To analyze the data, structural equation modeling was used. The software used is Smart PLS2. The results of structural equation model showed that negative attitudes, Inability to Creativity, personality traits, lack of motivation, religious beliefs and individual disqualification have a positive and significant effect on research misconduct. According to the findings of this study, Individual injury to n research misconduct (negative attitude, Inability to Creativity, personality traits, lack of motivation, religious beliefs, and individual disqualification), can be identified by identifying these factors. It provides solutions to reduce these injuries.